2002
DOI: 10.1289/ehp.021101185
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium in blood and urine--impact of sex, age, dietary intake, iron status, and former smoking--association of renal effects.

Abstract: We studied determinants of cadmium status and kidney function in nonsmoking men and women living on farms in southern Sweden. Median blood Cd (BCd) was 1.8 nmol/L (range, 0.38-18) and median urinary Cd (UCd) was 0.23 nmol/mmol creatinine (range, 0.065-0.99). The intake of Cd per kilogram body weight did not significantly differ between sexes and did not correlate with BCd or UCd, which may be explained by a low and varying bioavailibility of Cd from food items. However, when a subgroup of the study population,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
190
6
9

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 369 publications
(231 citation statements)
references
References 38 publications
26
190
6
9
Order By: Relevance
“…The level of U-Cd reported for the contaminated sites in this study was similar to those reported in a moderately contaminated area in Wenzhou, eastern China (Jin et al, 2002), the level of U-Cd in the control site was higher than those reported in Sweden (Olsson et al, 2002), and much lower than those reported elsewhere in China (Cai et al, 1990;Watanabe et al, 1998Watanabe et al, , 2000Jin et al, 2002). In the two reported Cd-contaminated sites in China, farmers produced their own rice at the time when the investigation was conducted, and rice was considered as the main source of Cd intake for the local people (Cai et al, 1990;Nordberg et al, 1997;Jin et al, 2002).…”
Section: Discussionsupporting
confidence: 87%
“…The level of U-Cd reported for the contaminated sites in this study was similar to those reported in a moderately contaminated area in Wenzhou, eastern China (Jin et al, 2002), the level of U-Cd in the control site was higher than those reported in Sweden (Olsson et al, 2002), and much lower than those reported elsewhere in China (Cai et al, 1990;Watanabe et al, 1998Watanabe et al, , 2000Jin et al, 2002). In the two reported Cd-contaminated sites in China, farmers produced their own rice at the time when the investigation was conducted, and rice was considered as the main source of Cd intake for the local people (Cai et al, 1990;Nordberg et al, 1997;Jin et al, 2002).…”
Section: Discussionsupporting
confidence: 87%
“…Table 3 lists recent studies linking iron status with blood and urine Cd. Most of the studies (Å kesson et al 2002;Berglund et al 1994;Kippler et al 2009;Nawrot et al 2008;Nishijo et al 2004;Olsson et al 2002) found a significant increase in body Cd stores in individuals with lower iron status. In Europe, iron deficiency is considered to be one of the main nutritional deficiency disorders affecting large fractions of the population, including, pre-postmenopausal and pregnant women.…”
Section: Bioavailability Of CD In the Intestine And Its Transfer To Bmentioning
confidence: 99%
“…Los valores medios o medianos de cadmio en orina observados en hombres y mujeres respectivamente, son muy similares a los aportados por otros estudios recientes de la República Checa 6 o de gran Bretaña 29 , aunque son superiores a los observados en Suecia 11 y en EEUU 8 . En nuestro estudio las mujeres presentaron niveles medios de cadmio en orina más elevados que los hombres, 0,62 µg/g creatinina en mujeres y 0,45 µg/g creatinina en hombres, aspecto que se repite en la literatura científica 6,8,11,29 . Una posible explicación a los elevados niveles de cadmio en las mujeres es que su absorción aumenta a medida que los niveles de hierro disminuyen 27 .…”
Section: Discussionunclassified
“…Una posible explicación a los elevados niveles de cadmio en las mujeres es que su absorción aumenta a medida que los niveles de hierro disminuyen 27 . El aumento de los niveles de CdU con la edad, independientemente del sexo, observado en este estudio fue también previamente descrito 11 . Asimismo, este estudio muestra que las personas de clases sociales más elevadas, clases I y II, presentan niveles de cadmio en orina más elevados con respecto a las clases más bajas, hecho que podría explicarse por su mayor consumo de productos de origen vegetal 30 .…”
Section: Discussionunclassified
See 1 more Smart Citation